Determination of Erucamide Slip Additive in Polypropylene Masterbatch: Comparison of Soxhlet and Dissolution-Precipitation Method - Purwaningtyas, Eka Listari; Wahyuni, Debby; Yanuar Ramadhan, Muhammad; Veni Susanti, Silfi; Naufal Ariesta, Muhammad; Aulia Agustina, Laily; Febriani, Rakhma (The Journal of Pure and Applied Chemistry Research, 2024)
Erucamide is a long-chain carboxylic acid amide used as a slip agent in plastic films. In this research, the slip additive in polypropylene masterbatch with 6% erucamide content was extracted by comparing two methods which are dissolution-precipitation and the Soxhlet method. The variant of sonication times in the dissolution-precipitation method and extractor-solvents in the Soxhlet method were done to determine the optimum parameter in each method. The examination of slip additive content in each extraction method used the KBr Disk-FTIR and the weight loss of sample analysis. The form of the sample, which was in the granule and powder form was also studied. Based on the result, the dissolution-precipitation method with 3 minutes of sonication times and the use of ethyl acetate as extractor solvent in the Soxhlet method gave a closer result for additive content in the masterbatch. The powder form of the sample also gave better results than the granule form for the extraction of erucamide. The Soxhlet method in the powder form showed comparable results with the dissolution-precipitation method by KBr Disk-FTIR analysis and higher results by weight loss analysis. By comparing the two methods of extraction, the Soxhlet method showed more robustness and efficiency for extraction of erucamide additive in polypropylene masterbatch than the dissolution-precipitation method.